Web-based and mobile-based new student admission and registration system for high school students - Hilfy Cipta Pratama; Adam Sekti Aji (Institute of Computer Science (IOCS), 2026)
The design of the Student Admission Information System (PPDB) is an effort by business organizations, including SMA 1 Parigi, to remain competitive with other schools. Information architecture serves as an organizational resource that ensures information systems and technology operate in alignment with organizational goals. This condition encourages SMA 1 Parigi to develop a business information system tailored to the institution’s needs. In this study, a needs analysis was conducted through a series of system modeling diagrams to plan the development of the information system using the Flutter Framework. To achieve the school’s goals as stated in its vision and mission, it is necessary to design and establish an information architecture model that integrates an information system in accordance with the school’s business requirements, particularly for SMA 1 Parigi. The Flutter Framework, as an information system service management framework, assists the organization in managing information systems from various perspectives by identifying and mapping business processes that underpin infrastructure and services.